2019
DOI: 10.1177/0170840619867360
|View full text |Cite
|
Sign up to set email alerts
|

Designing the Tools of the Trade: How corporate social responsibility consultants and their tool-based practices created market shifts

Abstract: Combining insights from the sociology of markets and studies of consultants, this article examines the tool-based practices by which market actors enable the agencing of the supply and demand of the market in ways that shape the market’s trajectory. Building on 31 interviews and a rich set of secondary data, we provide an analysis of the development of a market for consultancy products and services for corporate social responsibility (CSR) in the province of Quebec (Canada). Through analytical induction we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 39 publications
(63 reference statements)
0
41
0
Order By: Relevance
“…Jean-Pascal Gond: From different research projects Gond 2014, 2018;Ghadiri et al 2015;Gond et al 2018a), we found that CSR practitioners from different fields (responsible investing, CSR consultancy, and CSR management) resemble more to each other than to their organizational peers. They are 'like-minded' professionals, who share a strong progressive value-set, have acquired a growing knowledge-base, and are affiliated with similar fieldlevel associations (e.g.…”
Section: R E T H I N K I N G P R O F E S S I O N a L I Z A T I O Nmentioning
confidence: 92%
See 4 more Smart Citations
“…Jean-Pascal Gond: From different research projects Gond 2014, 2018;Ghadiri et al 2015;Gond et al 2018a), we found that CSR practitioners from different fields (responsible investing, CSR consultancy, and CSR management) resemble more to each other than to their organizational peers. They are 'like-minded' professionals, who share a strong progressive value-set, have acquired a growing knowledge-base, and are affiliated with similar fieldlevel associations (e.g.…”
Section: R E T H I N K I N G P R O F E S S I O N a L I Z A T I O Nmentioning
confidence: 92%
“…CSR practitioners: reflecting and foreshadowing new ways toward professionalism In recent years, a growing number of scientific publications have been focusing on the phenomenon of CSR practitioners (Bondy 2008;Tams and Marshall 2011;Wright and Nyberg 2012;Strand 2013;Brès and Gond 2014;Mitra andBuzzanell 2017, 2018;Risi and Wickert 2017;Wickert and de Bakker 2018), especially as CSR literature faces an emerging 'micro-turn' (Gond et al 2017;Jones and Rupp 2018;Wang et al 2016). However, knowledge on these practitioners is still scant.…”
Section: N E W W a Y S T O W A R D P R O F E S S I O N A L I Z A T I mentioning
confidence: 99%
See 3 more Smart Citations